2019
DOI: 10.12806/v18/i1/r2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Principal Investigators’ Differences in Leadership Style and Perceptions of Teamwork to Leverage Leadership Development

Abstract: The purpose of this study was to begin exploring the nature of leadership behavior and style, as it relates to team functionality. The extent to which the problems we face grow and become more complex; solutions require multiple perspectives, requiring researchers to be prepared to lead large groups of collaborators from a variety of disciplines. This study sought to explore the self-perceptions of principal investigators related to their leadership style and team functionality. Using the Multifactor Leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Previous research has shown that women typically self-assess teamwork competence greater than men (Al-Alawneh et al, 2011;De Paola & Scoppa, 2018;Rosch et al, 2014;Stedman & Pope, 2019;Strom & Strom, 2011). However, previous research has also shown that women may self-assess their competence more harshly than their male peers.…”
Section: Gendermentioning
confidence: 98%
See 2 more Smart Citations
“…Previous research has shown that women typically self-assess teamwork competence greater than men (Al-Alawneh et al, 2011;De Paola & Scoppa, 2018;Rosch et al, 2014;Stedman & Pope, 2019;Strom & Strom, 2011). However, previous research has also shown that women may self-assess their competence more harshly than their male peers.…”
Section: Gendermentioning
confidence: 98%
“…What this suggests is that being a man predicts lower self-assessed teamwork competence, despite higher scores in other key predictor variables. The research literature offers some explanation for this phenomenon, as there have been several examples of women self-assessing teamwork skills at a higher rate than men (Al-Alawneh et al, 2011;De Paola & Scoppa, 2018;Rosch et al, 2014;Stedman & Pope, 2019). Past research has shown that women lead in a more participative manner than men, are less likely to self-promote, and more likely to serve as social facilitators (Eagley & Karau, 1991;van Engen & Willemsen, 2004).…”
Section: Predictors Of Teamwork Competence In Agriculture Facultymentioning
confidence: 99%
See 1 more Smart Citation